(untitled) (Kateb International Journal of Economics and Management, 2023)
The banking system plays a crucial role in the economy today, as banks collect individuals’ capital and make it available to investors, thereby creating a conducive environment for economic growth and development in the country. The objective of this research is to evaluate the performance of the Islamic Bank of Afghanistan (Bakhtar Bank) before and after its conversion to Islamic bank. Based on the balance sheet data of the bank from 2015 to 2020, the study examines and compares the banking health index of the Islamic Bank and the former Bakhtar Bank. Additionally, the Islamic Bank of Afghanistan is compared to the Afghanistan National Bank, the International Bank of Afghanistan, Afghan United Bank, and Ghazanfar Bank, which operate in a mixed manner. Furthermore, the study investigates the contracts present in the Islamic Bank of Afghanistan. The analytical-descriptive method has been employed in this research. The results indicate that Bakhtar Bank performs better than the Islamic Bank of Afghanistan in terms of capital adequacy, management quality, and profitability, while the liquidity index is higher in the Islamic Bank compared to Bakhtar Bank. The capital adequacy and management quality indices of the Islamic Bank of Afghanistan (former Bakhtar Bank) are higher compared to mixed banks, particularly the International Bank of Afghanistan, and lower compared to other banks. The profitability index is higher in mixed banks than in the Islamic Bank of Afghanistan, and the liquidity index is lower in all mixed banks compared to the Islamic Bank of Afghanistan. The contracts used in the Islamic Bank of Afghanistan are Islamic contracts, and their transactions are free from usury (riba).